Physical Activity, Diet Compliance with Diabetic Ulcer Incidence in Hospital Makassar City - Nur Yazlim; Nur Juliana; Elna Sari; Rasniah Sarumi (Politeknik Karya Persada Muna, 2021)
Baground: Diabetic foot ulcers are a chronic complication of diabetes in the form of open wounds on the skin surface The prevalence of diabetic foot ulcers in Indonesia is around 13% of patients treated in hospitals and 26% of outpatients. The aimed was to determine relationship between physical activity, dietary compliance with the incidence of diabetic ulcers in Hospital Makassar City. Methods: This type of research used an analytic observational method with a cross sectional study design. Research were taken by accidental sampling and obtained 78 respondents. Data collection is done by filling out questionnaires. The data were analyzed by chi square fisher's exact test. Results: The results showed that the age of the with the highest incidence of diabetic ulcers was between 45-60 years was (57,7%) and the lowest was >60 years (42,3%), Women were susceptible to the incidence of diabetic ulcers (62,8%), the highest level of education was high school, namely 50% and the lowest was elementary school ( 1,3%) and employment is dominated by private employees (26,9%) and the lowest is civil servants (11,5%). From 46 respondents with less physical activity (71,8%) rexperienced the incidence of diabetic ulcers, while from 32 respondents in the moderate category (28,2%) experienced diabetic ulcers, p value = 0,019. From 42 respondents in the dietary compliance category, there were (71,8%) experiencing the incidence of diabetic ulcers, from 11 respondents in the diet-adhering category there were (28,2%) experiencing the incidence of diabetic ulcers, obtained a p value of 0,001. Conclusion: There are a significant relationship between physical activity, dietary compliance with the incidence of diabetic ulcers in Hospital Makassar City. Keywords: Diabetic ulcer, physical activity, diet compliance Abstrak Pendahuluan: Luka kaki diabetik adalah komplikasi kronik diabetes berupa luka terbuka pada permukaan kulit. Prevalensi terjadinya luka kaki diabetes di Indonesia sekitar 13% penderta dirawat di Rumah Sakit dan 26% penderita rawat jalan. Tujuan penelitian untuk mengetahui hubungan aktivitas fisik, kepatuhan diet terhadap kejadian ulkus diabetik di RSUD Kota Makassar. Metode: Jenis penelitian menggunakan metode observasional analitik dengan rancangan cross sectional study. Responden penelitian diambil dengan accidental sampling dan didapat 78 responden. Pengambilan data dilakukan dengan pengisian kuisioner. Data tersebut dianalisis dengan chi square fisher's exact test. Hasil: Hasil penelitian menunjukkan bahwa usia responden dengan kejadian ulkus diabetik tertinggi antara 45-60 tahun (57,7%) dan terendah >60 tahun (42,3%), berdasarkan jenies kelamin wanita rentan terhadap kejadian ulkus diabetik (62,8%), tingkat pendidikan terbanyak SMA yaitu 50% dan terendah SD (1,3%), pekerjaan didominasi oleh pegawai swasta (26,9%) dan terendah PNS (11,5%). Dari 46 responden dengan aktivitas fisik kurang terdapat (71,8%) responden mengalami kejadian ulkus diabetik sedangkan dari 32 responden dengan kategori cukup (28,2%) mengalami kejadian ulkus diabetik nilai p value = 0,019. Dari 42 responden dengan kategori kepatuhan diet, terdapat (71,8%) mengalami kejadian ulkus diabetik sedangkan dari 11 responden dengan kategori patuh diet terdapat (28,2%) mengalami mengalami kejadian ulkus diabetik, diperoleh nilai p 0,001 Kesimpulan: Ada hubungan signifikan antara aktivitas fisik, kepatuhan diet dengan kejadian ulkus diabeti RSUD Kota Makassar. Kata kunci: Ulkus diabetik, aktivitas fisik, kepatuhan diet